A visual step-by-step guide for clinicians to use video consultations in mental health services: NHS examples of real-time practice in times of normal and pandemic healthcare delivery. (December 2020) - Johns, Gemma; Tan, Jacinta; Burhouse, Anna; Ogonovsky, Mike; Rees, Catrin; Ahuja, Alka
Abstract : Despite the increasingly widespread use of video consultations, there are very few documented descriptions of how to set up and implement video consultations in real-time practice. This step-by-step guide will describe the set-up process based on the authors' experience of two real-time National Health Service (NHS) examples: a single health board use (delivered in normal time), and an All-Wales National Video Consultation Service roll-out (delivered during an emergency pandemic as part of the COVID-19 response). This paper provides a simple visual step-by-step guide for using telepsychiatry via the remote use of video consultations in mental health services, and outlines the mandatory steps to achieving a safe, successful and sustainable use of video consultations in the NHS by ensuring that video consultations fit into existing and new NHS workflow systems and adhere to legal and ethical guidelines.